Facile Synthesis of Mn-Doped ZnO Porous Nanosheets as Anode Materials for Lithium Ion Batteries with a Better Cycle Durability - Wang, Linlin (Nanoscale Res Lett, 2015)
Porous Zn(1 − x)Mn(x)O (x = 0.1, 0.2, 0.44) nanosheets were prepared by a low-cost, large-scale production and simple approach, and the applications of these nanosheets as an anode material for Li-ion batteries (LIBs) were explored. Electrochemical measurements showed that the porous Zn(0.8)Mn(0.2)O nanosheets still delivered a stable reversible capacity of 210 mA h g(−1) at a current rate of 120 mA g(−1) up to 300 cycles. These results suggest that the facile synthetic method of producing porous Zn(0.8)Mn(0.2)O nanostructure can realize a better cycle durability with stable reversible capacity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-015-0983-3) contains supplementary material, which is available to authorized users.